Ethnomedical Use Of Calotropis Procera (Aiton) Dryand. In Kaduna State Of Nigeria And Biological Evaluation (Applied Biological Research, 2023)
The development of current healthcare system is greatly influenced by plants having  therapeutic potential, especially the medicinal plants. The advent of new ailments  worldwide has encouraged the researchers to explore the potential of different plant  parts as well. The research aims to compile information on Calotropis procera  traditional usage and biological activity from a native population in the northern  Nigeria, Kaduna state. Random sampling was employed for the collection of  traditional medicinal knowledge on C. procera. Radical scavenging activity, ferric  reducing antioxidant power, and disk diffusion assay was employed to evaluate its  biological activity of ethanol and aqueous extracts of C. procera. The study revealed  that C. procera is traditionally used in the area to treat a variety of ailments like  hypertension, migraine, and spiritual problems having the highest fidelity at 0.9%.  The leaves exhibited highest radical scavenging, ferric reducing power, and  antibacterial activity at 86.01 µg ML-1 and 18.1 mmol g-1. The largest zone of inhibition  against Pseudomonas aeruginosa was found in an ethanol leaf extract of C. procera at  23.5 mm. The study revealed the leaf of C. procera as a good avenue for the  development of modern drugs.
Keywords: Antioxidants; antimicrobial; Calotropis procera; respondents; traditional knowledge